An evaluation of electronic and paper distance learning packages for practice based healthcare staff - Lee, Karen; Lee, John (Proceedings of the International Conference on Networked Learning, 2006)
A national educational package was produced for practice-based healthcare staff, for which web-based delivery was designed as the preferred option. A paper-based version was also made available. This study aims to examine staff reasons for choice of delivery mode and explore their experience of using the learning materials. Results from questionnaires show that despite an apparent higher degree of computer literacy than the general population, where given a choice, 66% staff chose paper-based in preference to web-based delivery. The most common reasons supplied were lack of computer skills and lack of computer access. It also appears of concern that 33% of those choosing web-based delivery did not complete the package. These issues will be further explored by focus groups.